2015
DOI: 10.1002/ajh.24099
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine treatment for patients with myelodysplastic syndrome and acute myeloid leukemia with chromosome 3q abnormalities

Abstract: Acute Myeloid Leukemia (AML) and myelodysplasia (MDS) with chromosome 3q abnormalities have a dismal outcome either untreated or with conventional treatments. Azacitidine (AZA) is now considered as the standard of care in high-risk MDS and oligoblastic AML patients. The objective of this study was to evaluate the impact of azacitine treatment in this cytogenetic subgroup. We report here a multicentre retrospective study of 157 patients treated with AZA for AML/MDS with chromosome 3q abnormalities and 27 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The observation that dysplastic myeloid features are retained in different maturation stages in MDS patients suggests a potential hierarchical model for dysplastic hematopoeisis (see harbored similar mutations found in leukemic cells. This mutation were observed at lower allele frequencies (4-31%), 20 suggesting a multipotent stem cell disease initiating effect. 21 These mutations, originated in the HSC compartment, can clonally expand and progress as preleukemic fractions, contribute to acute AML, an evolving concept that highlights a hierarchical model for MDS.…”
Section: Dysplastic Hematopoeisismentioning
confidence: 88%
“…The observation that dysplastic myeloid features are retained in different maturation stages in MDS patients suggests a potential hierarchical model for dysplastic hematopoeisis (see harbored similar mutations found in leukemic cells. This mutation were observed at lower allele frequencies (4-31%), 20 suggesting a multipotent stem cell disease initiating effect. 21 These mutations, originated in the HSC compartment, can clonally expand and progress as preleukemic fractions, contribute to acute AML, an evolving concept that highlights a hierarchical model for MDS.…”
Section: Dysplastic Hematopoeisismentioning
confidence: 88%
“…The SNFMI registry included 123 MDS/CMML patients with AID in 26 centres) [13], while the GFM registry included 4202 MDS/CMML in 30 centres of whom 80 also had documented AID. The GFM registry has been so far the basis for many publications of the GFM or that included the GFM [14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…36 This effect is particularly seen in those with chromosome 3q abnormalities, which are associated with resistance to conventional chemotherapy and for which azacitidine has been shown to be effective. 37 Several studies have suggested that gene mutations can impact prognosis, such as TET2, which was associated with increased survival after treatment with azacitidine, 38 DNMT3A with improved response after treatment with decitabine, 39 and TP53 with improved response after treatment with a 10-day schedule of decitabine. 40 Guadecitabine is a hypomethylating dinucleotide of decitabine linked to guanosine.…”
Section: Intensive Chemotherapymentioning
confidence: 99%